Determination of Haematological Effects of Extracts of Reseda sphenocleoides Leaves in Albino Rats Infected with Entamoeba histolytica - Mehdi, Mansour Abdulnabi Hadi; Pradhan, Vidya; Farooqui, Mazahar; Alarabi, Fadel Yousif Salah; Omar, Gozif Mohammed Nasr (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: This research was designed to examine improvements in some heamatological parameters of Entamoeba histolytica-infected rats treated with extracts of Reseda sphenocleoides leaves. Methods: Twenty rats weighing between 200-220 g were divided into 4 groups (Each per group containing 5 rats). Fifteen rats were infected by oral administration (17×103 cell/ml) of E. histolytica obtained from the stool. Infected rats were classified in differentiated three groups A, B, C. In addition, the negative control group E. The groups (A and B) were administered with the ethanolic and aqueous extracts at the dose of 500 mg/kg body weight/day, the group C was administered with metronidazole, in a dose 500 mg/kg body weight (Positive control group). The negative control group E was uninfected and untreated. The hematological parameters in the different groups were monitored throughout the period of study which was 10 days on three stages. Results: The results show a significant increase at P≤0.05 in Red Blood Cell Count (RBC), Haemoglobin (Hb), Hematocrit (HCT), Mean Cell Volume (MCV), Red Cell Distribution Width (RDW), Procalcitonin Test (PCT) and Lymphocyte (LY) in groups which treated with R. sphenocleoides extracts compare with metronidazole drug and the negative control group during treatment stages. While the results show a decrease of significant at P≤0.05 in Platelet (PLT), Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), Total White Blood Cell (WBC), Monocyte (MO) and Granulocytes (GR) in groups which treated with R. sphenocleoides extracts in comparison with the control groups of rats. The results also indicate no changes of significance at P>0.05 in Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC) during treatment stages. Conclusion: The findings of this study, the efficiency of R. sphenocleoides extracts in improving blood standards in rats infected with E. histolytica.
Keywords: Reseda sphenocleoides; Extract; Entamoeba histolytica; Haematological; Albino rats